Comparison of C2N Diagnostics' Aβ40, 42, and 42/40 ratio in Plasma Stored in Micronic and Sarstedt Tubes. (20th December 2022) - Edler, Michael C.; Russ, Kristen A; Mitchell, Colleen M.; Holubasch, Mary S.; Kirmess, Kris; Meyer, Matthew R.; Yarasheski, Kevin E.; Foroud, Tatiana M.; Dage, Jeffrey L.
Abstract: Background: Variation in biospecimen collection, processing, and storage parameters can introduce pre‐analytical variables that may confound interpretation of biomarker results. Samples collected under different study protocols or over a long period of time may require different labware, such as storage tubes. Comparability of storage tubes is necessary to better interpretate data collected both longitudinally within studies and across studies that may utilize various labware. The focus of this experiment was to perform comparability studies between plasma biomarkers measured in two polypropylene tube types: Sarstedt tube (72.694.006) and an automation friendly Micronic tube (MP52755). Methods: Blood was collected from healthy controls (N=23) and Alzheimer's Disease (AD) subjects (N=16) by the Indiana Biobank. Participants' brain amyloid status was unknown. Plasma from the same subjects was aliquoted (0.5 mL) into both Micronic and Sarstedt polypropylene tubes following standard NCRAD protocols and then frozen and stored at ‐80 °C for <7 months prior to analysis. Blinded samples were thawed once and analyzed for ApoE proteotype, Aβ40 and Aβ42 using liquid chromatography‐high resolution tandem mass spectrometry (LC‐MS/MS; C2 N Diagnostics, St. Louis, MO). Data was analyzed in JMP 16.0.0 with the method comparison add‐in and GraphPad PRISM 9.3.1 to determine comparability of the measurements made in the two sample tube types. Results: Comparability analysis found a high correlation of measured Aβ40, Aβ42 and the Aβ42/Aβ40 ratio in plasma stored in Micronic and Sarstedt tubes. Correlation analysis revealed slopes and intercepts within 95% confidence limits of 1 or 0 respectively. Bland Altman analysis showed low measurement bias (4‐7%) between the two tube types. ApoE isoform specific proteotypes were identical between tube types for all subjects. Conclusion: Results of the tube type study were within the validated performance range of the measurements. Plasma stored in Micronic and Sarstedt tubes can be used interchangeably when detecting ApoE proteotype and quantifying Aβ40 and Aβ42 concentrations using C2 N's LC‐MS/MS analytical platform. These results support the efforts of large biorepositories, like NCRAD to transition the storage of biospecimens from the larger, less automation friendly Sarstedt tube to the more automation friendly, freezer‐space saving Micronic tube. Supported by U24 AG021886 and UL1TR002529.